(untitled) (Global Journal of Human-Social Science, 2016)
Without any doubt rural-urban migration of the rural land owners has its own implication on the development process of both in urban and rural areas of a country. Hence, the primary purpose of this paper is to identify the determinants contributing for rural-urban migration of the rural land owners and its negative impact on rural development in Hulet Eju Enese Woreda of Eastern Gojjam zonal administration. The study further focused on the chara-cteristics of migrants and challenges they face at the destination. To achieve the objectives, both primary and secondary data were employed. Data collection instruments like structured questionnaire, semi-structured interview and secondary sources were largely employed. To this end, a total of 110 migrants were selected through purposive snow ball sampling technique for the survey and the data was analyzed both qualitatively and quantitatively. The result of this study revealed that both rural push and urban pull factors were determinants for rural land owners to migrate to Mota town from different parts of Hulet Eju Enese Woreda.